EU Equality Law and Precarious Work - Bell, Mark (Hart Publishing, 2019)
The late 1990s/early 2000s were a period of dynamism within EU Law that saw the adoption of the Racial Equality and Employment Equality Directives, as well as the enhancement of existing Directives on gender equality. In the same period, EU Labour Law witnessed the emergence of a new body of legislation governing non-standard forms of work, notably the 1997 Part-Time Work Directive and the 1999 Fixed-Term Work Directive. These were later joined, with some delay, by the 2008 Agency Work Directive. From the outset, it was clear that there were connections between these branches of EU Law: notably, there was already considerable case-law tackling the conditions of part-time work via indirect sex discrimination. Yet the two bodies of law were generally treated as conceptually distinct. This paper explores developments since 2000 to consider how EU Equality Directives interact with the legislation on non-standard forms of work. It examines whether the combination of both enhances legal protection in a harmonious and complementary fashion, or whether their internal differences lead to divergence in the manner in which each is interpreted and applied. To this end, the paper will concentrate on two examples. First, it will look at EU gender equality law. This already provided protection for (some) part-time workers, so it is relevant to scrutinise the impact of adding an alternative legal remedy in the form of the Part-Time Work Directive. Secondly, it considers the provisions on age discrimination within the Employment Equality Directive. A variety of cases have exposed how both younger and older workers can experience precarity in the labour market. For example, national law might afford employers more flexibility in the use of fixed-term contracts for those who work beyond the normal retirement age. This exposes the interrelationship of age discrimination provisions and the standards found in the Fixed-Term Work Directive. In conclusion, the paper aims to clarify the connections between these branches of EU Labour Law and to reflect critically on the way in which they are combined within the case-law of the CJEU. Given the salient debate around the perceived spread of precarious work in the wake of the economic crisis, the regulatory role played by EU Equality Law in this area warrants further scrutiny
EU Anti-Discrimination Law Beyond Gender
Keywords: Equality; Precarious work; Gender; Age; Part-time; Fixed-term; Inclusive Society; International Development; Equality; Equality law; Equality rights; employment equality law; eu equality law; precarious work